Enabling Complex Modulation of Directly Modulated Signals Using Laser Frequency Chirp - Di Che; Qian Hu; Feng Yuan; Qi Yang; Shieh, William (IEEE photonics technology letters, 2015)
Directly modulated laser (DML) with direct detection (DD) dominates the commercial optical short reach applications. When upgrading the DML-DD to higher data rate, the frequency chirp is commonly regarded as a performance barrier. On the contrary, in this letter, we take advantage of the chirp to generate phase modulation along with the intensity, namely, realize complex modulation at transmitter using a single DML. Coherent detection (CD) is applied to recover this 2 dimensional (2-D) signal. A modified Viterbi algorithm (VA) conducts maximum likelihood decoding utilizing the signal intensity and differential phase in receiver digital signal processing (DSP). By making decision using 2-D information, VA provides more than 9-dB optical signal to noise ratio (OSNR) sensitivity advantage over the conventional DML-CD with intensity only decision, in a 10-GBaud pulse-amplitude modulation (PAM)-4 system. We demonstrate the first PAM-8 experiment over 160-km standard single mode fiber using the phase diversity DML.